Tinjauan Hukum Terhadap Anak Pelaku Tindak Pidana Yang Membawa Senjata Tajam di Tempat Umum - Yusnandi, Yudi; Mirwansyah, Mirwansyah; Hendryan, Dery (Universitas Sang Bumi Ruwa Jurai, 2024)
Children's behavior is a joint responsibility of parents, family, school and society, so that if there is a deviation in children's behavior, such as being the perpetrator of possessing sharp weapons, there needs to be a role for these elements. In criminology, the child's behavior can be influenced by one of these elements, be it family, school, society and so on. Because in general children imitate what happens and sees behavior, so it is possible that children's behavior as users of sharp weapons is imitated by one of the existing elements. The problems in this research include: What is the legal review of the ownership of sharp weapons owned by children? What are the legal consequences for children who own sharp weapons? Legal review of ownership of sharp weapons owned by children in Indonesian law. The Criminal Code does not regulate the ownership of sharp weapons. This criminal act is regulated in the provisions of the Emergency Law of the Republic of Indonesia Number 12 of 1951. Legal consequences for children who own weapons sharp, namely that the child will be held accountable for his actions before the law, to be tried and receive punishment as a consequence of his actions. The legal consequences for children who own sharp weapons are that the child will be held accountable for his actions before the law, to be tried and receive punishment as a consequence of his actions.